PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN SISA LEBIH PERHITUNGAN ANGGARAN TERHADAP BELANJA MODAL PADA KABUPATEN YANG ADA DI PROVINSI SUMATERA UTARA PERIODE 2017-2021 - Sinaga, Monika Romasari; Purba, Imelda Rimenda (Jurnal Ilmiah Akuntansi (JIMAT), 2024)
This study aims to determine the effect of Regional Original Revenue, General Allocation Fund, and Remaining Budget Calculation Surplus on Capital Expenditures in Regencies in North Sumatra Province for the period 2017-2021. The population of this study were 25 regencies in North Sumatra Province. The sampling method used was purposive sampling method, so that 6 districts were obtained with a 5-year research period. The research method used is quantitative using secondary data sourced from the website of the Directorate General of Fiscal Balance of the Republic of Indonesia. The data analysis technique used is descriptive statistics, then classical assumption testing, multiple regression analysis and hypothesis testing. Based on the discussion, it shows that Regional Original Revenue has a positive and significant effect on Capital Expenditure, this can be seen from the partial test calculation obtained from the tcount value of 3.333 with a significance value of 0.003. General Allocation Fund has no effect on Capital Expenditure, this can be seen from the partial test calculation obtained from the tcount value of -0.446 with a significance value of 0.659. And, SiLPA has no effect on Capital Expenditure, this can be seen from the partial test calculation obtained from the tcount value of -0.348 with a significance value of 0.731. Simultaneously, Regional Original Income, General Allocation Fund, and SiLPA have a positive and significant effect on Capital Expenditure, this can be seen from the simultan test calculation obtained from the f-count value of 6,174 with a significance value of 0,003.